2012
DOI: 10.1016/j.jmr.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Frequency dependence of electron spin relaxation times in aqueous solution for a nitronyl nitroxide radical and perdeuterated-tempone between 250MHz and 34GHz

Abstract: Electron spin relaxation times of perdeuterated tempone (PDT) 1 and of a nitronyl nitroxide 2-(4-carboxy-phenyl)-4,4,5,5-tetramethylimidazoline-3-oxide-1-oxyl) 2 in aqueous solution at room temperature were measured by 2-pulse electron spin echo (T2) or 3-pulse inversion recovery (T1) in the frequency range of 250 MHz to 34 GHz. At 9 GHz values of T1 measured by long-pulse saturation recovery were in good agreement with values determined by inversion recovery. Below 9 GHz for 1 and below 1.5 GHz for 2, T1~ T2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 44 publications
4
20
0
Order By: Relevance
“…Studies of the frequency dependence of spin-lattice relaxation for carbon-centered trityl radicals (Owenius et al, 2005), nitrogen-centered nitroxide radicals (Biller et al, 2013; Biller et al, 2012; Hyde et al, 2004), and semiquinones (Elajaili et al, 2014) in fluid solution have demonstrated the significance of additional relaxation mechanisms. These frequency-dependent processes modulate anisotropic interactions – g anisotropy (Eq.…”
Section: Contributions To Electron Spin Lattice Relaxation and Dependmentioning
confidence: 99%
“…Studies of the frequency dependence of spin-lattice relaxation for carbon-centered trityl radicals (Owenius et al, 2005), nitrogen-centered nitroxide radicals (Biller et al, 2013; Biller et al, 2012; Hyde et al, 2004), and semiquinones (Elajaili et al, 2014) in fluid solution have demonstrated the significance of additional relaxation mechanisms. These frequency-dependent processes modulate anisotropic interactions – g anisotropy (Eq.…”
Section: Contributions To Electron Spin Lattice Relaxation and Dependmentioning
confidence: 99%
“…These studies have now been extended to a wider range of nitroxides and solvents to investigate i) the relative importance of spin rotation and modulation of nitrogen hyperfine anisotropy when τ R = 4 to 50 ps at ambient temperature, ii) whether additional mechanisms contribute to relaxation at frequencies lower than ∼9.5 GHz, and iii) the thermally-activated process that is proposed to have maximum impact on T 1 at 1 to 2 GHz, and has been observed previously in both the fast [21] and slow tumbling regimes [22]. T 1 and T 2 were measured by pulsed methods for the nitroxides shown in Figure 1, at frequencies between 250 MHz and 34 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we reported T 1 and T 2 for aqueous solutions of a nitronyl nitroxide and of PDT at five frequencies between 250 MHz and 34 GHz [21] in the fast motional regime where the tumbling correlation time, τ R , is less than about 25 ps. These studies have now been extended to a wider range of nitroxides and solvents to investigate i) the relative importance of spin rotation and modulation of nitrogen hyperfine anisotropy when τ R = 4 to 50 ps at ambient temperature, ii) whether additional mechanisms contribute to relaxation at frequencies lower than ∼9.5 GHz, and iii) the thermally-activated process that is proposed to have maximum impact on T 1 at 1 to 2 GHz, and has been observed previously in both the fast [21] and slow tumbling regimes [22].…”
Section: Introductionmentioning
confidence: 99%
“…The nitronyl nitoxide 32 was used as another example of wide spectrum imaging, but has been used in the past for spin-trapping of NO •33,34 . Imaging of a phantom containing nitronyl is shown in Figure 5 (C, D).…”
Section: Representative Resultsmentioning
confidence: 99%